Losers of globalization, losers in representation? The impact of education on unequal policy representation in Europe - Tsatsanis, Emmanouil; Belchior, Ana Maria (The Greek Review of Social Research, 2023)
The article focuses on the impact of education on policy representation. It examines degrees of congruence between political elites and citizens on policy preferences across different policy issues, trying to discern whether there is a representation gap between the so-called “winners” and “losers” of globalization in Europe as captured via the proxy measure of educational attainment. Additionally, we examine whether this representation gap, as well as overall levels of congruence, are affected by contextual factors related to the economy and the ideological orientation of governments. Using data from the 2014 European Election Studies and the 2014 Chapel Hill Expert Survey, our findings largely confirm the existence of a representation gap along educational lines. Contextual factors related to the economy present weak or no direct and moderating effects whereas ideologically left-leaning governments accentuate, for the most part, the representation gap between individuals of low and high educational attainment.